1969
DOI: 10.1111/j.1365-2672.1969.tb00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mode of Action of Some Cephalosporin Derivatives

Abstract: 7.(s-benzylthioacetamido)-cephem-3-ylmethyl~~~dimeth~ldithiocarbamate~4carboxylic acid (cephalosporin 7/30) prevented benzylpenicillin from inducing spheroplasts in Escherichia coli, and inhibited growth of preformed spheroplasts. These effecrs were also noted with dimethyldithiocarbamate (DMDT), the side-chain at position 3 in 7/30. Cephalosporin 7/30 inhibited growth of protoplasts of Bacillus megaterium and &.repto-COGCUB faeculis. At high concentrations, 7-[(2-thienyl)acetamido]-cephem-3-ylmethyl-Ndimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
8
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
4
8
0
Order By: Relevance
“…The finding that 7/30 and DMDT are inhibitory to mycoplasmas supports the observations reported by Fountain & Russell (1969). Compound 7/30 appears to affect processes other than cell wall synthesis as mycoplasmas do not have a cell wall.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The finding that 7/30 and DMDT are inhibitory to mycoplasmas supports the observations reported by Fountain & Russell (1969). Compound 7/30 appears to affect processes other than cell wall synthesis as mycoplasmas do not have a cell wall.…”
Section: Discussionsupporting
confidence: 86%
“…DJIDT has antibacterial action and preliminary experiments show that it has an PVIIC in broth of 1.5 pglml €or a strain ofStaphylococcus aureus and one of Streptococcus pyoqeiies. As found by Fountain & Russell (1969) the MIC for enterobacteriaceae may be high Sensitivity tests on horse blood agar using filter paper discs containing 10 pg of UXDT gave zones of inhibition with Llaemophilus infiuenxae that were slightly narrowcr than with the strain of Strep. pyogenes and zones with Xtrpp.…”
Section: Discussionmentioning
confidence: 72%
“…A possible reason for this, namely, the liberation onto or in the bacterial cell of dimethyldithiocarbamate (DMDT), which occupies position 3 in the 7/30 molecule (Fig. 1), was suggested previously (7).…”
mentioning
confidence: 86%
“…Cephalosporin 7/30 [7-(S-benzylthioacetamido)-cephen-3-ylmethyl-N-dimethyldithiocarbamate-4-carboxylic acid)] inhibited the growth of E. coli, but did not reveal the bacteriolytic action (5). It is also reported that cephalosporin 7/30 inhibited the protein synthesis of E. coli (4). The mode of action of SCE-129 against P. aeruginosa needs further investigation.…”
Section: C Until Usementioning
confidence: 99%
“…It has been reported that cephalosporins, like penicillins, are inhibitors of cell-wall synthesis (1)(2)(3)(4)(5)16). The accumulation of N-acetylaminosugar in the cells of S. aureus treated with SCE-129 was observed at the concentration of 10 ,ug/ml, which did not affect the synthesis of DNA, RNA, and protein.…”
Section: C Until Usementioning
confidence: 99%